Dinamika Pekerja Muda Outsourcing: Kegembiraan dan Kerentanan Menuju Risiko Masa Depan - Ridwan Tajul Fahmi; Nanda Harda Pratama Meiji; Nur Hadi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Working is one of the hopes as well as an achievement for the transitional period of youth. The social, cultural, and economic contexts that are developing rapidly due to globalization and advances in science and technology have made the sphere of work also change. As a result, the outsourcing work system has become the right choice for young people to develop their careers. Using qualitative research methods with a biographical model, several young informants were selected to tell narratives related to their dynamic careers in several industries with an outsourcing system. Data were collected through in-depth interviews and observations on the activities carried out by these young workers—besides, some secondary data related to the world of work as the primary data support. From the results obtained, youth who work in the industrial sector with an outsourcing mechanism have quite a risk of being vulnerable in the future even though the transition period they are experiencing looks relatively smooth (after taking education directly to work). Their joy in their daily lives as young people seems to be able to encourage them to keep their enthusiasm for work even though the risks that exist in the future are uncertain and winding.